Voters as Fiscal Conservatives - Peltzman, S. (Quarterly Journal of Economics, 1992)
Voters penalize federal and state spending growth. This is the central result of my analysis of voting behavior in Presidential, Senatorial, and gubernatorial elections from 1950–1988. The composition of federal spending growth seems irrelevant. The vote loss to the President's party from an extra dollar of defense or nondefense spending is the same. However, in gubernatorial elections, expansion of state welfare spending exacts a disproportionate political price. Deficit financing of federal or state spending does not appear to matter politically. I conclude by discussing the obvious question of why government budgets have grown in the face of this voter hostility.